2013
DOI: 10.3109/02813432.2013.844405
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, and management of childhood functional abdominal pain in general practice

Abstract: ObjectiveTo (i) describe the proportion of children presenting with abdominal pain diagnosed by the GP as functional abdominal pain (GPFAP); (ii) evaluate the association between patient and disease characteristics and GPFAP; (iii) describe diagnostic management by the GP in children presenting with abdominal pain, and (iv) evaluate whether children with GPFAP fulfill diagnostic criteria for functional abdominal pain (FAP) as described in current literature: chronic abdominal pain (CAP) and the Rome III criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 19 publications
(25 reference statements)
0
58
0
9
Order By: Relevance
“…We found that three of the eight alarm symptoms we explored, namely heredity, defecation at night and bloody stools, were significantly more common in OGID than in FGID. Previous studies on paediatric alarm symptoms have been contradictory (), and the 2005 technical report from North American Society for Pediatric Gastroenterology, Hepatology and Nutrition rated alarm signs as evidence quality D .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that three of the eight alarm symptoms we explored, namely heredity, defecation at night and bloody stools, were significantly more common in OGID than in FGID. Previous studies on paediatric alarm symptoms have been contradictory (), and the 2005 technical report from North American Society for Pediatric Gastroenterology, Hepatology and Nutrition rated alarm signs as evidence quality D .…”
Section: Discussionmentioning
confidence: 99%
“…There is expert consensus and a long tradition on the use of alarm symptoms to rule out organic disease . Studies on the paediatric Rome III criteria in combination with alarm symptoms are scarce and, to our knowledge, there has only been one validation study .…”
Section: Introductionmentioning
confidence: 99%
“…Досить час-то затяжний або рецидивуючий перебіг гастро-інтестинальних захворювань кишечника у дітей призводить до розвитку недостатності травлення, глибоких метаболічних порушень, затримки фі-зичного та психомоторного розвитку, формування полідефіцитних станів, зниження якості життя ди-тини [15,24]. Функціональні захворювання є пре-диктором формування хронічної патології ШКТ у подальші періоди життя, що визначає необхідність удосконалення методів їх лікування.…”
Section: âñòóïunclassified
“…Warschburger et al 35 Transversal 5 Schurman et al 39 Transversal 5 Lozinsky et al 12 Clinical trial 1 Spee et al 15 Transversal 2, 3…”
Section: Transversalmentioning
confidence: 99%